Correlation Analysis Between MTHFR C677T Polymorphism and Uterine Fibroids: A Retrospective Cohort Study - Shen, Jiahui; Jiang, Yanhui; Wu, Fengzhi; Chen, Hui; Wu, Qiujing; Zang, Xiaoxiao; Chen, Le; Chen, Yong; Yuan, Qiwen (Frontiers in Oncology, 2021)
Background: Uterine fibroids(UF) are the most common benign tumors in women, with high incidence and unknown causes. We aimed to explore the correlation between Methylenetetra-hydrofolate reductase (MTHFR) C677T polymorphism and UF. Methods: This is a retrospective cohort study. Data were collected from 2411 women detected for MTHFR C677T polymorphism in the Fifth Affiliated Hospital of Sun Yat-sen University from 2018 to 2020. B-ultrasound (BU) and the first page of medical records were used to analyze whether they had ever been diagnosed with UF. The collected data were analyzed. Using the chi-square test and regression analysis to explore the correlation, and the risk factors was screened by multifactor logistic regression analysis. Results: A total of 2411 pregnant women were in the MTHFR C677T polymorphism detection. Among them, 226(9.37%) were diagnosed as UF by BU or clinical diagnosis. The allele and genotype of MTHFR C677T were significantly different between the case and control group(P<0.05), and the distribution of the allele was following Hardy-Weinberg(H-W) equilibrium. Comparing with the wild-type (C/C), the mutant group (C/T+T/T) was more likely to form UF(OR,1.43;OR95%CI, 1.07-1.89). After adjusting for confound- ings, the heterozygous mutant(C/T) was more susceptible to UF than the wild-type (aOR,1.41;aOR95%CI,1.41-1.91). In the case group, BMI, gravidity and parity were not associated with the size and number of UF and the MTHFR C677T polymorphism(P>0.05). However, Elderly was associated with the incidence of UF, especially the multiple UF (P<0.05). Conclusion:Our results found that MTHFR C677T polymorphism was associated with UF occurrence for the first time. This could imply that it may increase the risk of forming UF in women of gestational age.